Final Year Dissertations with a Musical Topic at the Faculty of Education, Albacete, Spain (University of Castilla-La Mancha) - de Moya-Martínez, María del Valle (2022)
Objective. To collect and analyze the bachelor theses supervised and defended in the Department of Music of the Faculty of Education in Albacete, Spain (UCLM). The study covered the period from the department implementation in 2012-2013 to the academic year 2018-2019. Methodology. The approach used was mainly quantitative and descriptive with a sample of 102 final year dissertations, of which 66 belong to the bachelor’s degree in Primary Education, 33 to the bachelor’s degree in Early Childhood Education, and 3 to the bachelor’s degree in Bilingual Primary Education (English). The following variables were analyzed: number of theses, academic years, research lines, and keywords in titles. Results. A steady continuity in the research output was observed in the overviewed period. The most researched lines included music and emotions (19.61%), music and information and communication technologies (15.69%), and music and special education (14.71%), while the least researched one was legislation on music education (2.94%). The analysis of the keywords of the titles showed a strong presence of the term emotion(s)/(al) in the bachelor’s degrees of Early Childhood and Primary Education Teaching. Some substantial differences were also found in the thematic preferences of both degrees, pointing to more theoretical and technical studies in Primary Education and more practical studies in Early Childhood. Conclusions. This paper analyzed and discussed the research lines of a sample of bachelor theses. The limitations of the sample offered preliminary results on the evolution of the research lines, which suggests differences between the thematic preferences between both degrees.